Antagonistic properties of Lactiplantibacillus plantarum MYSVB1 against Alternaria alternata: a putative probiotic strain isolated from the banyan tree fruit - Vasundaradevi, R.; Sarvajith, M.; Somashekaraiah, Rakesh; Gunduraj, Adithi; Sreenivasa, M. Y. (Frontiers in Microbiology, 2024)
Alternaria alternata, a notorious phytopathogenic fungus, has been documented to infect several plant species, leading to the loss of agricultural commodities and resulting in significant economic losses. Lactic acid bacteria (LAB) hold immense promise as biocontrol candidates. However, the potential of LABs derived from fruits remains largely unexplored. In this study, several LABs were isolated from tropical fruit and assessed for their probiotic and antifungal properties. A total of fiftyfive LABs were successfully isolated from seven distinct fruits. Among these, seven isolates showed inhibition to growth of A. alternata. Two strains, isolated from fruits: Ficus benghalensis, and Tinospora cordifolia exhibited promising antifungal properties against A. alternata. Molecular identification confirmed their identities as Lactiplantibacillus plantarum MYSVB1 and MYSVA7, respectively. Both strains showed adaptability to a wide temperature range (10-45 °C), and salt concentrations (up to 7%), with optimal growth around 37 °C and high survival rates under simulated gastrointestinal conditions. Among these two strains, Lpb. plantarum MYSVB1 demonstrated significant inhibition (p<0.01) of the growth of A. alternata. The inhibitory effects of cell-free supernatant (CFS) were strong, with 5% crude CFS sufficient to reduce fungal growth by >70% and complete inhibition by 10% CFS. Moreover, the CFS was inhibitory for both mycelial growth and conidial germination. CFS retained its activity even after long cold storage. The chromatographic analysis identified organic acids in CFS, with succinic acid as the predominant constituent, with lactic acid, and malic acid in descending order. LAB strains isolated from tropical fruits showed promising probiotic and antifungal properties, making them potential candidates for various applications in food and agriculture.